Effect of size sprinkled heat exchange surface on developing boiling - Kracík, Petr; Baláš, Marek; Lisý, Martin; Pospíšil, Jiří (SAGE Publications Ltd, 2016)
This article presents research of sprinkled heat exchangers. This type of research has become rather topical in relation to sea water desalination. This process uses sprinkling of exchangers which rapidly separates vapour phase from a liquid phase. Applications help better utilize low-potential heat which is commonly wasted in utility systems. Low-potential heat may increase utilization of primary materials. Our ambition is to analyse and describe the whole sprinkled exchanger. Two heat exchangers were tested with a similar tube pitch: heat exchanger no. 1 had a four-tube bundle and heat exchanger no. 2 had eight-tube bundle. Efforts were made to maintain similar physical characteristics. They were tested at two flow rates (ca 0.07 and 0.11 kg s-1 m-1) and progress of boiling on the bundle was observed. Initial pressure was ca 10 kPa (abs) at which no liquid was boiling at any part of the exchanger; the pressure was then lowered. Other input parameters were roughly similar for both flow rates. Temperature of heating water was ca 50°C at a constant flow rate of ca 7.2 L min-1. Results of our experiments provide optimum parameters for the given conditions for both tube bundles.

This article presents research of sprinkled heat exchangers. This type of research has become rather topical in relation to sea water desalination. This process uses sprinkling of exchangers which rapidly separates vapour phase from a liquid phase. Applications help better utilize low-potential heat which is commonly wasted in utility systems. Low-potential heat may increase utilization of primary materials. Our ambition is to analyse and describe the whole sprinkled exchanger. Two heat exchangers were tested with a similar tube pitch: heat exchanger no. 1 had a four-tube bundle and heat exchanger no. 2 had eight-tube bundle. Efforts were made to maintain similar physical characteristics. They were tested at two flow rates (ca 0.07 and 0.11 kg s-1 m-1) and progress of boiling on the bundle was observed. Initial pressure was ca 10 kPa (abs) at which no liquid was boiling at any part of the exchanger; the pressure was then lowered. Other input parameters were roughly similar for both flow rates. Temperature of heating water was ca 50°C at a constant flow rate of ca 7.2 L min-1. Results of our experiments provide optimum parameters for the given conditions for both tube bundles.
Effect of size sprinkled heat exchange surface on developing boiling
Keywords: boiling; droplet; heat transfer; sprinkled; Tube bundle; water; boiling; droplet; heat transfer; sprinkled; Tube bundle; water